2004
DOI: 10.1196/annals.1318.036
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Free Plasma DNA as a Prognostic Marker in Intensive Treatment Unit Patients

Abstract: Recent evidence suggests that cell-free plasma DNA has potential use as a prognostic marker in many clinical settings. The aim of the present study was to evaluate the prognostic role of cell-free plasma DNA in the prediction of clinical outcome in intensive treatment unit (ITU) patients. Cell-free plasma DNA was measured by real-time polymerase chain reaction assay for the beta-globin gene and SOFA score, APACHE II score, CRP concentrations, and clinical outcome (duration of stay, ventilation time, and mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 5 publications
9
64
3
Order By: Relevance
“…Our study was the first to demonstrate that rising or falling concentrations of plasma DNA were not related to the outcomes of patients with severe sepsis. Our results showing that nonsurvivors had higher plasma DNA concentrations than survivors are in agreement with earlier studies performed in intensive care patients (17)(18)(19). Rhodes et al (18 ) demonstrated in a critically ill patient population that patients who developed severe sepsis or septic shock had higher plasma DNA concentrations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study was the first to demonstrate that rising or falling concentrations of plasma DNA were not related to the outcomes of patients with severe sepsis. Our results showing that nonsurvivors had higher plasma DNA concentrations than survivors are in agreement with earlier studies performed in intensive care patients (17)(18)(19). Rhodes et al (18 ) demonstrated in a critically ill patient population that patients who developed severe sepsis or septic shock had higher plasma DNA concentrations.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, increased plasma levels of nucleosomes, in which fragmented DNA is packed during apoptosis, have been found in patients with severe sepsis and septic shock (16 ). Preliminary data from ICU patients suggest that admission plasma DNA concentrations may be higher in nonsurvivors than in survivors (17,18 ). We have recently shown that the maximum cell-free plasma DNA concentration in the first days of intensive care is independently associated with hospital mortality in critically ill patients (19 ).…”
mentioning
confidence: 99%
“…A correlation between cf-DNA and CRP (r = 0.36, P < 0.001) has also been demonstrated in intensive care unit patients. 41 Other research has found no correlation between cf-DNA and CRP. 42,43 Previous research in team sports such as soccer and rugby has shown that CRP and CK may not peak until 24-48 hours post competition, and may remain significantly elevated above baseline for several days.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between cf-DNA and CRP has been reported [12,25]. This correlation between cf-DNA and CRP suggests that cf-DNA may be a valuable indicator of inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…Hydration was measured via urinary specific gravity (USG) with a PAL-10S Refractometer (Atago, Tokyo, Japan). A USG ≥ 1.020 signifies dehydration (25), but no subject USG measurements were ≥ 1.020 at any of the 6 measurement times. Biochemical markers are quantified as concentrations in plasma or serum as well as percent change (%∆).…”
Section: Biochemistrymentioning
confidence: 99%